Effect of pre-treatment on physical properties and sensory attributes of gelatin extracted from sutchi catfish (Pangasius sutchi) Skin / Normah Ismail and Wan Najma Farhaten Wan A Latiff - Ismail, Normah; Wan A Latiff, Wan Najma Farhaten (Penerbit UiTM (UiTM Press), 2019)
This study was conducted to evaluate the effect of pre-treatment on the fishy flavour and odour removal of gelatine extracted from the skin of sutchi catfish (Pangasius sutchi). Pre-treatment of the skin involved soaking at 4°C in distilled water (GC), lime followed by tamarind (GLT) or salt followed by activated carbon (GSC) prior to extraction in warm distilled water (50°C) for 12 hours. Yield, physical properties and sensory were determined. Results showed that GLT produced highest yield (19.72%) compared to GSC (15.01%) and GC (15.81%). Although, GLT exhibited lowest gel strength (282.29g), viscoelasticity (14.1ºC) and setting point (10.46ºC) compared to other pre-treatments, fishy flavour and odour of the gelatine were almost absent with the score of 1.68 and 1.74, respectively. These values were below those of reference which are 1.87 (fishy flavour) and 2.71 (fishy odour) denoting from ‘absent to weak’. Since fishy flavour and odour were almost absent, soaking sutchi catfish skin in lime followed by tamarind could be a good method for achieving the desired sensory attributes of the freshwater fish by the reduction of the gelatine off flavour.